2002
DOI: 10.1111/1467-7679.00181
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Behaviour and Supermarkets in Argentina

Abstract: Globalisation, combined with structural adjustment (economic deregulation, market liberalisation, privatisation of public enterprises, etc.), have together created a new macroeconomic context in the past decade in Argentina. In this new context, the food market has undergone profound changes, requiring producers, processors, and distributors to carry out co-ordination and integration of the supply chain. To meet the new rules of the game, firms have had to adapt their production, processing, logistical, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 1 publication
1
18
0
3
Order By: Relevance
“…In a series of articles, Tom Reardon and colleagues have charted the rapid rise of supermarkets almost everywhere in the developing world and forecast their continued rapid spread (for example, Belik and dos Santos, 2002;Berdegué et al, 2004;Codron et al, 2004;Dries et al, 2004;Ghezan et al, 2002;Gutman, 2002;Hu et al, 2004;Neven and Reardon, 2004;Reardon and Berdegué, 2002;Reardon and Swinnen, 2004;Rodriguez et al, 2002;Schwentesius and Gómez, 2002;Weatherspoon and Reardon, 2003). The prime purpose of the articles has been to alert academics and policy-makers to the spread of supermarkets and the implications for supply chains, particularly involving fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of articles, Tom Reardon and colleagues have charted the rapid rise of supermarkets almost everywhere in the developing world and forecast their continued rapid spread (for example, Belik and dos Santos, 2002;Berdegué et al, 2004;Codron et al, 2004;Dries et al, 2004;Ghezan et al, 2002;Gutman, 2002;Hu et al, 2004;Neven and Reardon, 2004;Reardon and Berdegué, 2002;Reardon and Swinnen, 2004;Rodriguez et al, 2002;Schwentesius and Gómez, 2002;Weatherspoon and Reardon, 2003). The prime purpose of the articles has been to alert academics and policy-makers to the spread of supermarkets and the implications for supply chains, particularly involving fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…Terminologi perilaku konsumen didefinisikan sebagai perilaku dalam mencari, membeli, menggunakan, mengevaluasi, serta menghabiskan produk dan jasa yang diharapkan dapat memuaskan kebutuhan konsumen (Bettman et al 1998, Rodriguez et al 2002. Sementara itu, model proses pengambilan keputusan konsumen menguraikan perilaku dan pengambilan keputusan ke dalam tahapan-tahapan (a) identifikasi kebutuhan, (b) pencarian informasi, (c) evaluasi konsumen tehadap berbagai alternatif tersedia, (d) keputusan pembelian, dan (e) evaluasi pascapembelian.…”
Section: Adiyoga W: Faktor-faktor Yang Memengaruhiunclassified
“…A review by Rodriguez and others (2002) demonstrated that Argentinean consumers with higher education, income, durable assets, and consumer credit were more likely to shop at supermarkets where presumably processed foods are more readily available (as opposed to smaller, specialized shops). Also, residents of the poorer, more rural northern region of Argentina were less likely to shop at a supermarket.…”
Section: North and South Americamentioning
confidence: 99%